Modelagem de um Campus Virtual Inteligente para Navegação e Integração de Serviços - Maia, Hugo W.; Souza, Daniel F. L.; Castro, Angélica F. de (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2014: Anais Estendidos do XX Simpósio Brasileiro de Sistemas Multimídia e Web, 2014)
The advancement of internet allows the representation of real places through virtual environments. This paper presents the development of a 3D virtual campus that represents the Universidade Federal Rural do Semi-Árido called UFERSA Virtual. Through this environment, students, teachers and the entire community will have access to some services offered by the institution. One of services provided by UFERSA Virtual is the navigation between the structures of campus. The users will have the opportunity to meet structures of buildings, classrooms, as well as various other places that is part of university. In addition to navigation, other functionality provided by the smart campus is the video streaming recommendation service for distance learning. which will provide educational video content according to user preferences, previously registered. The virtual campus also supports the integration of virtual environment with real structures, allowing, for instance, the reading and control of real status of lamps.